Inter-State Compulsory Conciliation Procedures and the Maritime Boundary Dispute Between Timor-Leste and Australia. (22nd October 2018) - Kedgley Laidlaw, Anais; Phan, Hao Duy
Abstract: This article examines the origin and nature of the compulsory conciliation procedure under the 1982 United Nations Convention on the Law of the Sea (UNCLOS) and how it has played out in the conciliation between Timor-Leste and Australia—the first time this procedure has been triggered. The article identifies the features of the UNCLOS conciliation procedure—many of which are unique—that appear to have played a significant role in this success of this case and which could be useful for future disputes—including its compulsory nature, its procedural flexibility, its ability to take into account non-legal considerations, its 12-month deadline and its substantive reporting requirement. The article concludes by looking at the significance of this case for future disputes—highlighting that its implications go beyond UNCLOS, as many of the major multilateral environmental treaties, including the United Nations Framework Convention on Climate Change and Paris Agreement contain untested compulsory conciliation procedures that are similar to UNCLOS.